Diffusion-limited aggregates grown on nonuniform substratres - Ramirez Pastor, Antonio Jose (2013)
In the present paper, patterns of diffusion-limited aggregation (DLA) grown on nonuniform substrates are investigated by means of Monte Carlo simulations. We consider a nonuniform substrate as the largest percolation cluster of dropped particles with different structures and forms that occupy more than a single site on the lattice. The aggregates are grown on such clusters, in the range the concentration, p, from the percolation threshold, pc up to the jamming coverage, pj. At the percolation threshold, the aggregates are asymmetrical and the branches are relatively few. However, for larger values of p, the patterns change gradually to a pure DLA. Tiny qualitative differences in this behavior are observed for different k sizes. Correspondingly, the fractal imension of the aggregates increases as p raises in the same range pc ≤ p ≤ pj. This behavior is analyzed and discussed in the framework of the existing theoretical approaches.